Message from the Rector - Romero Revilla, Félix (2024)
It is a pleasure to welcome you to this edition of the magazine Perfiles de Ingeniería, a publication dedicated to exploring the development of engineering and its impact on today's society, so characterized by the relevance of technology and innovation.